2015
DOI: 10.2140/memocs.2015.3.385
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the active damping of suspension bridges

Abstract: This paper explores the feasibility of active damping of suspension bridges with the addition of stay cables controlled by active tendons. An active tendon consists of a displacement actuator collocated with a force sensor monitoring the tension in the cable. The active tendons are controlled by decentralized integral force feedback (IFF). In the first part of the paper, the potential of the control strategy is evaluated on a numerical model of an existing footbridge; several configurations are investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Suspension bridges and cable-stayed bridges require active damping to reduce the effects of various phenomena. Active damping solutions have been proposed in [43,200,2,1,37,22,205,204]. Active tendon control of cable-stayed bridges using hydraulic suspension is considered in [37].…”
Section: Notes and Referencesmentioning
confidence: 99%
“…Suspension bridges and cable-stayed bridges require active damping to reduce the effects of various phenomena. Active damping solutions have been proposed in [43,200,2,1,37,22,205,204]. Active tendon control of cable-stayed bridges using hydraulic suspension is considered in [37].…”
Section: Notes and Referencesmentioning
confidence: 99%
“…The above theory has been extended to guyed trusses and cable structures (Figure 8) [8][9][10][11], including suspension (pedestrian) bridges [12]. It was demonstrated that structures can be damped actively very efficiently with guy cables and, despite the simplifying assumption of the theory, the performances can be predicted with surprising accuracy from the results of two modal analyses, one including all of the cables (Figure 8 The maximum achievable damping in mode i is given, once again, by…”
Section: Guyed Trusses Cable Structuresmentioning
confidence: 96%
“…The AVC method was also found in civil infrastructures in which the review has been made by considering different types of application of civil structures that have been controlling piezoelectric material [45]. For the case of suspension bridges, an investigation has been made for the active damping controlled by decentralized integral force feedback [46] and, similarly, model frame structures, [47] including smart model frames [48] and loop share buildings [49], are also controlled.…”
Section: Vibration Controlmentioning
confidence: 99%